2012
DOI: 10.1504/ijpp.2012.045869
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home research in Jinan, China: a focus group approach

Abstract: This qualitative research using the focus group approach has gathered pertinent perceptions from the stakeholders in Chinese elderly care environment, including community-based and institutionalised elderly, medical providers, administrators and governmental officials. The study found that the elderly are willing to live in nursing homes when they are not in good physical condition and are dependent on others for their activities of daily living. The utilisation of nursing home care has gained acceptance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Most of the NH staff received little professional training in elder care [5,23e25]. Newly recruited direct caregivers were trained mainly by more experienced staff which did not follow standardized or knowledge-based training plans [11,26]. Existing training programs, regardless of being led by NHs, Government agencies, or Bureau of Civil Affairs, focused on providing daily care and basic knowledge about common diseases among older adults [25].…”
Section: Staff Qualification Standardsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the NH staff received little professional training in elder care [5,23e25]. Newly recruited direct caregivers were trained mainly by more experienced staff which did not follow standardized or knowledge-based training plans [11,26]. Existing training programs, regardless of being led by NHs, Government agencies, or Bureau of Civil Affairs, focused on providing daily care and basic knowledge about common diseases among older adults [25].…”
Section: Staff Qualification Standardsmentioning
confidence: 99%
“…Basic services were provided, including personal care, basic medical care, room cleaning, meals, and laundry [5,11,23,26]. Wu et al [3] found four different care levels in participating NHs; they classified residents by the level of independence, ranging from totally independent to totally dependent in daily living.…”
Section: Care By Nh Staffmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Taking Shandong Province as an example, the highest occupancy rate is 100% and the lowest only 20%. 38 This situation is further aggravated by China's lack of a central allocation system at any administrative level or formal eligibility criteria governing admission to residential care homes. As there is no clear and consistent definition of residential care and a mixed model of care is adopted to provide services to older persons with different degrees of functional dependency, residential care homes are free to adopt discriminatory admission policies to reject frail and highly dependent applicants.…”
Section: Three Promising Policy Directions To Better Foster a New Socmentioning
confidence: 99%